2005
DOI: 10.1080/09553000600555389
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effects of TETRA RF fields on intracellular calcium in neurones and cardiac myocytes

Abstract: Overall, these results showed no evidence of any consistent or biologically relevant effect of TETRA fields on [Ca(2 + )](i) in granule cells and cardiac myocytes at any of the SAR tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…Schwartz et al [1990] reported an increased calcium efflux in whole frog hearts. Other studies, however, have not reported altered calcium physiology in neurons or cardiac tissue due to EMF [Schwartz and Mealing, 1993;Wolke et al, 1996;Green et al, 2005]. Some studies have focused on the direct effects on electrophysiological properties during the course of exposure [Caddemi et al, 1986].…”
Section: Discussionmentioning
confidence: 94%
“…Schwartz et al [1990] reported an increased calcium efflux in whole frog hearts. Other studies, however, have not reported altered calcium physiology in neurons or cardiac tissue due to EMF [Schwartz and Mealing, 1993;Wolke et al, 1996;Green et al, 2005]. Some studies have focused on the direct effects on electrophysiological properties during the course of exposure [Caddemi et al, 1986].…”
Section: Discussionmentioning
confidence: 94%
“…Using a SAR of 2 W/kg and a GSM signal (915 MHz), Cranfield et al [2001] found that calcium concentration in Jurkat cells did not change during 10 min of exposure. In a recent study, Green et al [2005] did not find any effect on [Ca 2þ ] i in rat cerebellar neurons and cardiac myocytes, using a TETRA signal (0.4 W/kg) and a longer time (20 min) of exposure. A very recent study carried out in ratcultured hippocampal neurons has shown that chronic exposure (15 min/day for 8 days) to GSM signal (1800 MHz, 2.4 W/kg) decreased both amplitude of aamino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) miniature excitatory post-synaptic currents, and the expression of post-synaptic density 95 [Xu et al, 2006].…”
Section: Discussionmentioning
confidence: 94%
“…More recent studies using direct measurements of [Ca 2þ ] i on different cells did not show significant changes following RF exposure. In particular, no effects were observed in guinea pig ventricular myocytes [Wolke et al, 1996], Jurkat leukemic T-cells [Cranfield et al, 2001], rat cerebellar granule cells, and cardiac myocytes [Green et al, 2005].…”
Section: Introductionmentioning
confidence: 96%
“…which are also eigenfunctions of the Hamiltonian, degenerated with (5). Once more, we refer to [1] for further discussion.…”
Section: Formalism and Plasmamentioning
confidence: 99%
“…There is, of course, a vast amount of literature on biological effects of electromagnetic radiation. Some more recent examples are [3][4][5][6][7]. It is not the purpose of this study to discuss these papers; a recent review, including many references, is given in [8].…”
Section: Introductionmentioning
confidence: 99%